Metastatic Ampullary Adenocarcinoma Presenting as a Hydrocele: A Case Report - Lane, Whitney O; Bentley, Rex C; Hurwitz, Herbert I; Howard, Leigh A; Polascik, Thomas J; Anderson, Mark R; Blazer, Dan G (JOP. Journal of the Pancreas, 2014)
Context Metastases from ampullary malignancies are common, but spread to the testicle and paratesticular tissue is exceedingly rare with only 2 reported cases in the literature. Case Report We report a case of a 70 year-old male with a history of ampullary adenocarcinoma status post pancreaticoduodenectomy who presented with a symptomatic right-sided hydrocele. Subsequent pathology revealed metastatic ampullary adenocarcinoma. Conclusions Metastasis to the testicle and paratesticular tissue from ampullary malignancies is rare, but must be considered in the evaluation of scrotal masses in patients with a history of ampullary malignancy. Image: Right-sided inguinal fluid collection at CT scan.